Animal breeding strategies can improve meat quality attributes within entire populations. (October 2017) - Berry, D.P.; Conroy, S.; Pabiou, T.; Cromie, A.R.
Abstract: The contribution of animal breeding to changes in animal performance is well documented across a range of species. Once genetic variation in a trait exists, then breeding to improve the characteristics of that trait is possible, if so desired. Considerable genetic variation exists in a range of meat quality attributes across a range of species. The genetic variation that exists for meat quality is as large as observed for most performance traits; thus, within a well-structured breeding program, rapid genetic gain for meat quality could be possible. The rate of genetic gain can be augmented through the integration of DNA-based technologies into the breeding program; such DNA-based technologies should, however, be based on thousands of DNA markers dispersed across the entire genome. Genetic and genomic technologies can also have beneficial impact outside the farm gate as a tool to segregate carcasses or meat cuts based on expected meat quality features. Highlights: Ample genetic variation exists in meat quality to justify inclusion in breeding programs. Traditional genetic evaluations have contributed to massive gains in performance. Genetic gain can be augmented by incorporating DNA information into genetic evaluations. Genetic and genomic tools have many benefits over and above their application to animal breeding.